Działalność szkolnego Towarzystwa Czytelniczego w Gimnazjum Mariackim w Szczecinie w XIX i pierwszych dekadach XX w. Z dziejów kultury książki w dawnym Szczecinie - Janina Kosman (Z Badań nad Książką i Księgozbiorami Historycznymi, 2021)
St. Mary's Gymnasium in Szczecin, one of the oldest high schools in the city, has a rich history. An interesting trend in the school's history is represented by the school's interest groups. Among the oldest and most numerous are choirs and recitation groups, some dating back to the 18th century. Other groups, with a specific profile and programme, also developed systematically. In the 19th century reading societies (Leseverein) were particularly active in the gymnasium. The tradition of these societies continued into the 20th century. It fits into the broader context of Szczecin's school theatres. Their activities can be traced on the basis of information contained in printed school reports, which give the programme of activities of school interest groups and specify their participation in school calendar celebrations. Valuable material are the archives stored in the State Archives in Szczecin concerning St. Mary's Gymnasium, including documents created by members of the reading society.